Investigation of parameters affecting the formation of the bushing and bushing wall obtained in the friction drilling process - Ozek, Cebeli; Bal, Muhammet (Pamukkale Univ, 2020)
Friction drilling is an important non-traditional manufacturing method with the effect of heat caused by friction on a work piece-tool interface with a rotating tool. The purpose of this method is to increase the length of the connection through the bushing formed in the lower part of the hole in the thin-walled sheets. In this study, it is aimed to investigate the effects of material thickness and tool diameter on bushing height (ha), bushing wall thickness (hc) and micro hardness change in friction drilling method. In experiment studies, tungsten carbide (WC) tools were used with taper angle of phi=36 degrees, the tool diameters of empty setd=5 mm, empty setd=10 mm, empty setd=15 mm and empty setd=20 mm. Friction drilling was applied to St37 steel with a thickness of t=2 mm, t=4 mm, t=6 mm, t=8 mm and t=10 mm. The experiments were carried out at a speed of n=1120 rpm and a feed rate of f=25 mm/min. The effects of material thickness and tool diameter on bushing height bushing outer diameter, bushing shapes and changes in micro hardness were investigated. The largest bushing height of ha=15.30 mm, the lowest bushing wall thickness of hc=4.25 mm and the highest micro hardness of 183 HV was obtained. It was observed that material thickness and tool diameter had a significant effect on bushing wall thickness and bushing height, but micro hardness values did not change much.
Keywords: Friction drilling; Bushing height; Bushing Wall thickness